The impact of environmental characteristics of place as sense of place elements on atmosphere perception: focusing on P/N evaluations of atmosphere experienced by Japan undergraduate in leisure places - Changguk Kim; Dongyun Kwak (Journal of Asian Architecture and Building Engineering)
The study of the relationship between the atmosphere of a place and the emotional response of users has been a key focus of traditional sense of place research. While place attachment, image, and behavioral intention have been extensively discussed through various methodologies, the atmosphere of a place has received relatively little attention. The concept of atmosphere is complex and difficult to define, but it is one of the most valuable research themes due to the significant impact that places have on our lives. This study proposes atmosphere as an analytical indicator of sense of place and uses phenomenological discussions from previous studies to conceptualize it and verify its validity as a quantitative indicator. By modeling the characteristics of a place through 10 indicators that were determined to be capable of measuring sense of place through previous studies, statistical significance was found in some independent variables. This finding demonstrates the potential of quantitative studies to complement qualitative studies, which have been the dominant approach in this field. This approach not only enriches traditional qualitative methodologies but also establishes a framework for future investigations into the atmospheric dimensions of place, offering a comprehensive study method for evaluating sense of place.